2021
DOI: 10.1108/ijse-07-2020-0496
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing investor behavior: an empirical study of Saudi Stock Market

Abstract: PurposeThe objective of the study is to determine the factors influencing the behavior of investor in Saudi Stock Market.Design/methodology/approachThe paper uses correlation analysis, factor analysis, reliability and multiple regression analysis on the primary data collected from 125 investors in Saudi Stock Market through a questionnaire distributed randomly.FindingsThe results indicate that the factors like past performance of the stocks, financial statements, firm status in industry, the reputation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 12 publications
4
44
0
1
Order By: Relevance
“…Judgment sampling was considered appropriate for selecting the investors. The criteria for selecting the investors were as follows: (a) having an experience of at least five years of investing in financial markets, (b) investments in at least two investment products, (c) knowledge of investment behavior, and (d) they are endowed with the responsibility of making investment decisions in their family, The sample constituted 76% males and 24% females which is similar to the studies stating that most of the financial decisions are taken by male members of the family (Ritika and Kishor, 2020;Khawaja and Alharbi, 2021).…”
Section: Data Collectionmentioning
confidence: 91%
“…Judgment sampling was considered appropriate for selecting the investors. The criteria for selecting the investors were as follows: (a) having an experience of at least five years of investing in financial markets, (b) investments in at least two investment products, (c) knowledge of investment behavior, and (d) they are endowed with the responsibility of making investment decisions in their family, The sample constituted 76% males and 24% females which is similar to the studies stating that most of the financial decisions are taken by male members of the family (Ritika and Kishor, 2020;Khawaja and Alharbi, 2021).…”
Section: Data Collectionmentioning
confidence: 91%
“…However, Hirshleifer (2001) concluded that it is important to consider alternative factors that are related to human behaviour, such as psychology and sociology. These factors favour the investors' psychological profile rather than their financials (Khawaja and Alharbi, 2021). Researchers have ongoing attempts to contribute to the development of the investors' behavioural aspects of investment decisions.…”
Section: Behavioural Factorsmentioning
confidence: 99%
“…GCC markets are considered in the finance literature due to their importance to the global economy (Alnori et al, 2021;Bugshan et al, 2021). Some studies investigated the behavioural factors related to individual investors in the GCC setting (Abdullah and Hilu, 2015;Alsedrah and Ahmed, 2017;Khawaja and Alharbi, 2021;Matoussi and Mostafa, 2016). For instance, Matoussi and Mostafa (2016) examined the behavioural biases that influence Saudi investors in the main stock exchange (TASI).…”
Section: Individual Investors' Behavioural Factors In the Gcc Marketsmentioning
confidence: 99%
See 2 more Smart Citations